The sanitary condition of our national schools - Roche, Anthony (Statistical and Social Inquiry Society of Ireland, 1900)
That the health of the individual and the community depends largely on their surroundings being sanitary is now universally admitted. That this rule is specially applicable to the young, is acknowledged by all sanitarians, and that therefore their schools, wherein they spend so many hours, should meet all the requirements of modern sanitation will hardly be contested by anyone devoting any consideration to the subject. The growing and undeveloped structures of children, their close contact in schools for a number of hours, their less power of resistance to cold and other depressing influences, all render them remarkably susceptible to the causes and spread of disease. An inquiry, therefore, into the sanitary conditions of our National School is not alone interesting, but of great practical importance. According to the last Official report there are no less than 8,651 of these schools, and on their rolls 808,467 students. I have for some years been making personal observations and inquiries into the sanitation of these> schools, as, however, my sphere of observation has not extended over many parts of Ireland, I will rely rather on the evidence of the inspectors of these schools and on official returns. These inspectors have had ample and extended opportunities of observation, they cannot be expected to be prejudiced against the system of which they form a part and, therefore, when they speak so plainly of the unsanitary condition of many of these schools their opinon may be trusted as impartial. I will now read some extracts from the reports taken from the last available report of the Commissioners of National Education.
Read Tuesday, February 20th, 1900
Keywords: National education; Sanitary conditions; 314.15